Pengembangan Perangkat Pembelajaran IPA SMP Berbasis Discovery Learning Berorientasi Kemampuan Pemecahan Masalah dan Hasil Belajar Peserta Didik - Rahmania, Rahmania; Danial, Muhammad; Gani, Tabrani (Program Pasca Sarjana UNM, 2020)
This study is development research, which aims at developing Natural Sciences (IPA) learning tools for SMP (junior high school) based on discovery learning oriented on problem solving skills and learning outcomes on acidic-base and salt material which is valid, practical and effective. The development model employed in this study referred to 4D development model, which consisted of define, design, develop, and disseminate. The learning tools developed are RPP, LKPD, BAPD, Media, and THB. The IPA learning tools for SMP based on discovery learning which had been developed was then validated by two experts. After being validated, the test of learning tools based on discovery learning was conducted at SMPN 36 Makassar in grade VII.9 with the total of 32 students. The results of the study reveal that the learning tools based on discovery learning developed which had been validated indicates that the mean score is 3.74 which is in very valid criteria. The learning tools based on discovery learning is stated as practical and effective, because the results of the practically test reveal (1) the implementation of learning tools based on discovery learning is in the average of M = 1.9 in the category of (1.5 ≤ M ≤ 2.0) meaning that the aspects and criteria observed on the implementation of learning tools based on discovery learning is in entirely implemented category, (2) the teacher gave a very positive response on the learning tools based on discovery learning with the percentage of 92.07%, and (3) the students gave a very positive response on the learning tools based on discovery learning with the percentage of 92.77%. The learning tools is also met the criteria of effective with the following results: (1) the improvement of problem solving skills of students from 27.22% becomes 74.50%, (2) the learning outcomes has met effective criteria that the average of the percentage is 83.48% with the classical completeness 87.50%, whereas, the improvement of learning outcomes based on N-gain test is 0.82 with high criteria. Therefore, the results of the study shows that the product of learning tools developed is categorized as valid, practical, and effective.